Randomised Evaluation of modified Valsalva Effectiveness in Re-entrant Tachycardias (REVERT) study. Issue 3 (12th March 2014) - Appelboam, Andrew; Reuben, Adam; Mann, Clifford; Lobban, Trudie; Ewings, Paul; Benger, Jonathan; Vickery, Jane; Barton, Andrew; Gagg, James
Abstract : Introduction: The Valsalva manoeuvre (VM) is a recommended first-line physical treatment for patients with re-entrant supraventricular tachycardia (SVT), but is often ineffective in standard practice. A failed VM is typically followed by treatment with intravenous adenosine, which patients often find unpleasant. VM effectiveness might be improved by a modification to posture which exaggerates the manoeuvre's vagal response and reduces the need for further emergency treatment. Methods and analysis: This is a multicentre randomised controlled clinical trial in 10 UK emergency departments (EDs). It compares a standard VM with a modified VM incorporating leg elevation and a supine posture after a standardised strain in stable adult patients presenting to the ED with SVT. The primary outcome measure is return to sinus rhythm on a 12-lead ECG. Secondary outcome measures include the need for treatment with adenosine or other antiarrhythmic treatments and the time patients spend in the ED. We plan to recruit approximately 372 patients, with 80% power to demonstrate an absolute improvement in cardioversion rate of 12%. An improvement of this magnitude through the use of a modified VM would be of significant benefit to patients and healthcare providers, and justify a change to standard practice. Ethics and dissemination: The study has been approved by the South West—Exeter Research Ethics Committee (REC reference 12/SW/0281). The trial will be published in an international peer reviewed journal. Study findings will be sent to the European and International resuscitation councils to inform future revisions of arrhythmia management guidelines. Results: The trial will also be disseminated at international conferences and to patients through the Arrhythmia Alliance, a patient support charity. Registration: The study is registered with Current Controlled Trials (ISRCTN67937027 ) and has been adopted by the National Institute for Health Research (NIHR) Clinical Research Network.